2017
DOI: 10.1242/jcs.206847
|View full text |Cite
|
Sign up to set email alerts
|

Conserved cytoplasmic domains promote Hrd1 ubiquitin ligase complex formation for ER-associated degradation (ERAD)

Abstract: The mammalian ubiquitin ligase Hrd1 is the central component of a complex facilitating degradation of misfolded proteins during the ubiquitin-proteasome-dependent process of ER-associated degradation (ERAD). Hrd1 associates with cofactors to execute ERAD, but their roles and how they assemble with Hrd1 are not well understood. Here, we identify crucial cofactor interaction domains within Hrd1 and report a previously unrecognised evolutionarily conserved segment within the intrinsically disordered cytoplasmic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 74 publications
0
47
0
Order By: Relevance
“…To generate C‐terminally FLAG‐HA‐tagged CGRRF1 and Hrd1, the FLAG‐HA sequence was inserted into the pcDNA5‐FRT/TO vector (Invitrogen). Primers with HindIII and AgeI restriction site sequences were used to amplify the ORF of Hrd1 (Schulz et al , 2017) and CGRRF1 (MGC collection). The extended ORFs of Hrd1 and CGRRF1 were cloned into pcDNA5‐FRT/TO‐FLAG‐HA using HindIII and AgeI restriction enzymes.…”
Section: Methodsmentioning
confidence: 99%
“…To generate C‐terminally FLAG‐HA‐tagged CGRRF1 and Hrd1, the FLAG‐HA sequence was inserted into the pcDNA5‐FRT/TO vector (Invitrogen). Primers with HindIII and AgeI restriction site sequences were used to amplify the ORF of Hrd1 (Schulz et al , 2017) and CGRRF1 (MGC collection). The extended ORFs of Hrd1 and CGRRF1 were cloned into pcDNA5‐FRT/TO‐FLAG‐HA using HindIII and AgeI restriction enzymes.…”
Section: Methodsmentioning
confidence: 99%
“…To assess whether tagged ER-E3s faithfully reproduce endogenous complexes, we compared 25 the interaction profile of Hrd1 24,26,27,[47][48][49] with that of DOX-induced Hrd1-FH. Cofactors including SEL1L, FAM8A1, OS-9, Herp, and UBE2J1 were comparably coimmunoprecipitated (co-IPed) by both Hrd1 and Hrd1-FH ( Fig.…”
Section: Isolation and Discovery Of Er-resident E3 Interactorsmentioning
confidence: 99%
“…How we envisage E3 function at the ER has been shaped by extensive studies on the evolutionarily conserved Hrd1 [19][20][21][22][23][24][25][26] . With as many as eight TMDs 15 , a cytoplasmic RING domain and an extended C-terminus with low complexity 27 , Hrd1 scaffolds specialised lumenal, integral membrane, and cytosolic co-factors such as the AAA-ATPase VCP/p97 28,29 to form multi-component complexes that coordinate recognition, 15 retrotranslocation, and ubiquitination of misfolded secretory cargo 20,24 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further analysis revealed that two proteins (HSPA1L and HSPA5) that increased at the earliest stage were molecular chaperones for recognition of the un‐ or misfolded proteins which were over accumulated in the ER within 12 h. DNAJC3, which increased after 24 h, was mainly involved in the UPR to protect cells by attenuating general protein synthesis and reducing ER client protein load . After 48 h up to 72 h, four newly increased proteins, HSP90B1, HERPUD1, PDIA4 and HYOU1, could strengthen the activity of ERAD . Meanwhile, the increased HYOU1 has a key positive role in cytoprotective mechanisms triggered by hypoxia (the oxygen deficit started within 6 h of TM treatment, as shown in the analysis above) .…”
Section: Resultsmentioning
confidence: 99%